Christian theology an introduction. - McGrath, Alister E. 1953- (Malden Wiley-Blackwell, 2011)
"Alister McGrath's Christian Theology: An Introduction is one of the most internationally-acclaimed and popular Christian theology textbooks in use today. This 5th edition has been completely revised, and now features new and extended material, numerous additional illustrations, and companion resources, ensuring it retains its reputation as the ideal introduction to Christian theology.A revised 5th edition of the bestselling textbook, now completely up-to-date with expanded material, and packed throughout with student features and new illustrationsFeatures new sections on Copernicanism and DarwinismIncludes extended discussions of Augustine's doctrine of creation, Trinitarian theologies of religion, and the relation of Christianity to other faithsMay be used as a stand-along volume, or alongside the Christian Theology Reader, 4th edition for a complete overview of the subjectRetains the chapter structure of the 4th edition, ensuring comparatability with earlier editions and courses based on theseAccompanied by a revised instructor's website, featuring expanded resources including study questions and answers; visit www.wiley.com/go/mcgrath for more details and to register for access"--
"Alister McGrath's Christian Theology: An Introduction is one of the most internationally-acclaimed and popular Christian theology textbooks in use today. This 5th edition has been completely revised, and now features new and extended material, numerous additional illustrations, and companion resources, ensuring it retains its reputation as the ideal introduction to Christian theology. The revised 5th edition includes: Entirely new sections exploring Copernicanism and Darwinism Extended discussions of Augustine's doctrine of creation, Trinitarian theologies of religion, and the relation of Christianity to other faiths A number of additional illustrations and student-friendly features throughout Retains the chapter structure of the 4th edition, ensuring compatability with earlier editions and courses based on these A fully updated website available at www.wiley.com/go/mcgrath, featuring new student resources such as study questions and additional lectures from Alister McGrath Retaining its successful structure, but now expanded and updated to reflect invaluable reader feedback, Alister McGrath's Christian Theology offers an unparalleled introduction to the concepts and key developments of 2,000 years of Christian thought. It may be used as a stand-along volume, or alongside The Christian Theology Reader, 4th edition for a complete overview of the subject"--
Includes bibliographical references and index.
Keywords: Theology, Doctrinal